Letter from Robert S. Mulliken to Harrison Shull, 1958 - Mulliken, Robert Sanderson (1958)
Letter between Robert S. Mulliken and Harrison Shull, American quantum chemists.
Keywords: Shull, Harrison; Mulliken, Robert Sanderson; Chemists; Hyperconjugation; Nobel Prize winners; Physicists; Berry, R. Stephen